2017
DOI: 10.1177/0363546517726983
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Femoral and Acetabular Version Abnormalities in Patients With Symptomatic Hip Disease: A Controlled Study of 538 Hips

Abstract: Abnormalities in femoral version are highly prevalent in patients with hip pain who are eligible for hip preservation surgery, and severe abnormalities are prevalent in 1 of 6 patients (17%). Based on these results, the evaluation of young patients with hip pain should always include an assessment of femoral version and acetabular version to best decide what treatment approach should be undertaken to optimize outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
199
4
25

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(230 citation statements)
references
References 77 publications
2
199
4
25
Order By: Relevance
“…However, it was shown that femoral torsion considerably affects the impingement-free range of motion 65,66 and that severely abnormal femoral torsion may be present in one of six hips undergoing an MRI of the hip. 67 This is important because decreased femoral torsion yields worse outcomes after arthroscopic FAI correction and may require additional rotational femoral osteotomies in severe cases. 68 Femoral torsion has now been recognized as the third pillar of FAI and should be routinely measured.…”
Section: Impingement Morphologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was shown that femoral torsion considerably affects the impingement-free range of motion 65,66 and that severely abnormal femoral torsion may be present in one of six hips undergoing an MRI of the hip. 67 This is important because decreased femoral torsion yields worse outcomes after arthroscopic FAI correction and may require additional rotational femoral osteotomies in severe cases. 68 Femoral torsion has now been recognized as the third pillar of FAI and should be routinely measured.…”
Section: Impingement Morphologiesmentioning
confidence: 99%
“…125 It is commonly accepted that measurement of femoral torsion should be part of every preoperative evaluation for reconstructive hip surgery. 67 Orthopaedic surgeons traditionally relied on axial CT images to measure femoral torsion. 127 Due to the typically young patient age and the fact that patients with groin pain routinely undergo MRI, radia-tion-free measurements were introduced for MRI.…”
Section: Mri Protocolmentioning
confidence: 99%
“…Jahrhundert beschrieben [2]. Torsionsfehlstellungen können bei bis zu 52 % der Patienten mit einem symptomatischen FAI vorliegen [3]. Je nach femoraler Torsion kann ein Impingement der Hüfte verstärkt oder auch vermindert werden (▶ Abb.…”
Section: Torsionsfehlstellungenunclassified
“…So kann eine vermehrte femorale Torsion ein Impingieren bei azetabulärer Retroversion oder Cam-Deformität verringern (▶ Abb. 6)[3]. Umgekehrt kann eine tiefe femorale Torsion oder Retrotorsion einer exzessiven azetabulären Version entgegenwirken (▶ Abb.…”
unclassified
“…Abnormal femoral version is common in patients with labral tears, dysplasia, femoroacetabular impingement, cerebral palsy, and arthritis. It is present in 52% of patients with either symptomatic hip dysplasia or femoroacetabular impingement . A retroverted femur orientation is also associated with less improvement after reconstructive surgery for femoroacetabular impingement .…”
mentioning
confidence: 99%